A democracia das ruas: o caso das manifestações do Brasil (2014-2015) - Daniel, Vanessa Cristhina Zorek (2016)
In light of the new characteristics presented by the Brazilian democratic scenario caused mainly due to critical demonstrations towards the federal government, this thesis aims at reflecting on the nature of the democracy present on Brazilian streets. Therefore, we seek support in the liberal democratic theory in order to guide us as to the characteristics and the limits that this model offers to the contemporary democracy. Besides, we focus on the national political context that precedes the demonstrations occurred between October 2014 and March 2015 so as to understand in which extent the current demonstrations, focused on anti-corruption and antipetismo, were influenced by previous events such as the corruption scandals concerning the Workers Party (PT). For this reason, this research is characterized as an exploratory work that analyzes the factors that contributed or led the individuals to identify themselves as a group and to participate actively in the demonstration. We noticed that the questions raised can be associated to the corruption scandals and to the lack of benefits received by the traditional middle class during the time PT governed the country, not to mention the ideological setting. The demonstrations had their goals at exposing the corruption reports related to the Workers Party, diminishing the attention about corruption involving either other political parties or other instances of power. Furthermore, observed that there were no deep discussions and propositions made by the people who led those public acts; and also, the active citizenship expressed by these citizens is limited to the act of emphasizing their frustration and to demand the impeachment of the current president.